Strategies for engaging older adults and informal caregivers in health policy development: A scoping review - Opeyemi Rashidat Kolade; Joshua Porat-Dahlerbruch; Rustem Makhmutov; Theo van Achterberg; Moriah Esther Ellen (BMC, 2024)
Abstract Background Care for older adults is high on the global policy agenda. Active involvement of older adults and their informal caregivers in policy-making can lead to cost-effective health and long-term care interventions. Yet, approaches for their involvement in health policy development have yet to be extensively explored. This review maps the literature on strategies for older adults (65+ years) and informal caregivers' involvement in health policy development. Method As part of the European Union TRANS-SENIOR program, a scoping review was conducted using the Joanna Briggs Institute's methodology. Published and grey literature was searched, and eligible studies were screened. Data were extracted from included studies and analysed using the Multidimensional Framework for Patient and Family Engagement in Health and Healthcare. Results A total of 13 engagement strategies were identified from 11 publications meeting the inclusion criteria. They were categorized as "traditional", "deliberative" and "others", adopting the World Bank's categorization of engagement methods. Older adults and informal caregivers are often consulted to elicit opinions and identify priorities. However, their involvement in policy formulation, implementation and evaluation is unclear from the available literature. Findings indicate that older adults and their informal caregivers do not often have equal influence and shared leadership in policy-making. Conclusion Although approaches for involving older adults and their informal caregivers' involvement were synthesized from literature, we found next to no information about their involvement in policy formulation, implementation and evaluation. Findings will guide future research in addressing identified gaps and guide policy-makers in identifying and incorporating engagement strategies to support evidence-informed policy-making processes that can improve health outcomes for older adults/informal caregivers.